2022
DOI: 10.3390/molecules27030638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound-Assisted Extraction of Carotenoids from Papaya (Carica papaya L. cv. Sweet Mary) Using Vegetable Oils

Abstract: By-products from fruits and are of great interest for their potential use in the food industry due to their high content of bioactive compounds. Herein, we examined the ultrasound-assisted extraction (UAE) of carotenoid and carotenoid esters from papaya pulp and peel using soybean oil and sunflower oil as alternative green solvents. Response surface methodology (RSM) was established to optimize the UAE process. Three independent variables, ultrasonic amplitude (20–60%), time (10–60 min), and co-solvent percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
11
0
6
Order By: Relevance
“…For example, approximately 97.1% of carotenoids (astaxanthin, lutein and β-carotene) can be extracted through SFE by using ethanol as a co-solvent [75]. Our results were in agreement with previous reports of high yields when using EPE, CPE and UAE [76,77].…”
Section: Plant Pigments Total Polyphenols and Antioxidant Activity Of...supporting
confidence: 92%
“…For example, approximately 97.1% of carotenoids (astaxanthin, lutein and β-carotene) can be extracted through SFE by using ethanol as a co-solvent [75]. Our results were in agreement with previous reports of high yields when using EPE, CPE and UAE [76,77].…”
Section: Plant Pigments Total Polyphenols and Antioxidant Activity Of...supporting
confidence: 92%
“…Overall, BRS and GPP fortification did not have a negative effect on the viability of the LAB compared to the control. In fact, papaya pulp and peel have been reported to have antimicrobial properties (Lara‐Abia et al ., 2022; Wani & Uppaluri, 2022). However, in this study, adding papaya powder did not have a detrimental effect on LAB growth and activity.…”
Section: Resultsmentioning
confidence: 99%
“…The remarkable increase in TPC in fortified yoghurts is likely due to the presence of phenolic compounds in plant ingredients (Pelaes Vital et al, 2015;Zhang et al, 2019;Ahmed et al, 2021). Papaya contains a wide range of phytochemicals such as phenolic compounds, carotenoids, glucosinolates, and alkaloids (Leitão et al, 2022;Wani & Uppaluri, 2022). Besides, papaya seeds are a good source of phenolic compounds, including benzyl isothiocyanate, glucosinolates, β-carotene, and carotenoids (Leitão et al, 2022).…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In ripe papaya fruits, the main carotenoids identified are lycopene, β-cryptoxanthin and β-carotene, and there is evidence that these compounds reduce the incidence of degenerative diseases (Sancho;Yahia;González-Aguilar, 2011). Different studies have reported the extraction of carotenoid compounds combining the ultrasound process with vegetable oil as a solvent (Ordóñez-Santos; Pinzón-Zarate; González-Salcedo, 2015;Goula et al, 2017;Ordóñez-Santos;Girón;Rodríguez-Rodríguez 2019;Chutia;Mahanta 2021;Lara-Abia;Welti-Chanes;Cano, 2022). These researchers highlight the extraction efficiency, reducing solvent consumption, less extraction times and less energy consumption compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%